Fungsi dan Peran LKBH PGRI dalam Perlindungan Guru - Akhmad Gafuri (Milenial: Journal for Teachers and Learning, 2025)
This research aims to analyze the effectiveness of the implementation of legal protection for teachers based on the Teacher and Lecturer Law, identify the forms of legal threats faced, and formulate an integrative strengthening strategy model. Through a correlational descriptive quantitative approach with a sample of 210 teachers in Kotabaru City secondary education units, this research found that the effectiveness of implementing legal protection is still low, characterized by limited teacher access to legal aid and weak socialization of legal rights. Various legal threats have been identified, ranging from criminalization for disciplinary action, intimidation in assessments, civil lawsuits, to violations of Intellectual Property Rights, which are increasingly exacerbated by digital amplification. As a solution, the "Networked Teacher Legal Protection System" model was formulated which is oriented towards three pillars: preventive through socialization and standard protocols, responsive through strengthening LKBH PGRI as a first responder and uses technology, as well as curative assistance in the form of litigation legal assistance and psychological support. This model emphasizes sustainable synergy between teachers, schools, LKBH PGRI, and law enforcement officials to create an educational ecosystem that is safe and conducive to increasing teacher professionalism